Making a case for a development-driven approach to law as a linchpin for the post-2015 development agenda - Soyeju, Olufemi (My University, 2015)
The Millennium Development Goals (MDGs) are milestones on a long road to global development. They were adopted by consensus in 2000 as a policy framework to guide the global development process, ending poverty as the overarching goal. Time-bound, with quantified targets for addressing extreme poverty in its many dimensions, the goals have successfully drawn the attention of the world to the virulence of grinding poverty in low-income countries. However, with the deadline in plain sight it has become clear that many of the quantified targets set out in the Millennium Declaration (MD) in the year 2000 are no longer realistic. Recent reviews of the progress so far in achieving these goals suggest a marked discrepancy in outcomes across the regions. Besides, there are concerns that even if these set goals are met, new challenges have emerged with the potential of reversing whatever progress that has been made under the current development framework. For example, sub-Saharan Africa (SSA) as a region seems to be off-track in meeting these goals. While other regions of the world have made significant progress in achieving many of the goals, there is a widespread shortfall in the achievement of most of the MDGs in SSA countries. It is against this backdrop that there is an on-going process of articulating a new development agenda to consolidate and build on the successes of this current development framework, address new, pressing global concerns, and confront the shortfalls and gaps in the outcomes of the MDG framework. This paper argues that law has an inherent development function and can play a significant role in driving the proposed post-2015 development agenda. The paper therefore seeks to make a case for the adoption of a development-driven approach to law as a linchpin for the post-2015 development agenda.
Keywords: Law; Development; Development-driven law; Development law; Development goals; Development strategy; Millennium Development Goals; Millennium Declaration; Post-2015 development agenda; MDGs